Development and performance of the c4c national clinical trial networks for optimizing pediatric trial facilitation - Degraeuwe, Eva; van der Geest, Tessa; Persijn, Laura; Nuytinck, Lieve; Raes, Ann; Turner, Mark; Fernandes, Ricardo M.; Vande Walle, Johan; de Wildt, Saskia N.; , IMI2 project conect4children (c4c) consortium, including National Hubs/Networks Belgian Pediatric Clinical Research Network (BPCRN) (Belgium); Pedmed-NL (Netherlands) (Frontiers in Pediatrics, 2023)
Introduction The high failure rate of industry-driven pediatric clinical trials leads to insufficient timely labeling of drugs in children and a lack of scientific evidence, resulting in the persistently high off-label drug use. National clinical trial networks can facilitate collaboration between sites, investigators, and experts, increasing the likelihood of successful trials. Within the conect4children (c4c) network, an Innovative Medicines Initiative 2-funded project, National Hubs hosted by National Clinical Trials Networks were set up across 21 European countries to facilitate the setup and execution of pediatric clinical trials. In this paper, we aim to present the performance metrics of the trial feasibility process as well as learnings and challenges encountered by the Belgian and Dutch Networks in working within the European c4c project. Method The c4c National Hubs streamline pediatric clinical trials by initiating early country outreach, identifying overlapping studies, recommending quality trial sites, and supporting trial budgeting for both industry and academic settings. To show the impact of Pedmed-NL and Belgian Pediatric Clinical Research Network (BPCRN), internal metrics were collected from 2019 to 2022 on four industry-sponsored and three academic trials performed within the c4c network. Timelines and outcomes of the site identification were collected and analyzed for industry trials. A qualitative analysis was conducted through c4c platforms, sponsor interactions, and stakeholder engagement to evaluate the added value of a research network. Results In industry-sponsored trials, full feasibility questionnaires were completed within 2 weeks (n = 48), and inclusion rates were up to 80% of clinical sites. Before committing to c4c, 14% of sites were contacted by industry, leading to communication burdens. Utilizing national infrastructure knowledge and therapeutic environment insights helped optimize trial timelines and address feasibility challenges. In addition, national adaptations, such as bilingual staff and site development, played a role in streamlining trial operations in both academic and industry settings. Performance and experiences were similar for both networks. Conclusion The early-facilitation examples from the c4c trials demonstrated promising metrics for two National Hubs, including optimized start-up timelines and aiding site selection quality. The learnings and challenges of the Belgian and Dutch Networks provided insights for the development of clinical research networks.